Decolonizing Academia: Poverty, Oppression, and Pain - Smith-Cruz, Shawn(ta) (Radical Teacher, 2019)
Book Review of Decolonizing Academia by Clelia O. Rodríguez. The author was invited to keynote a closed symposium on libraries and open pedagogies by the reviewer who was personally affected by the reading of the text.